A review of technological innovations leading to modern endovascular brain aneurysm treatment - Lauzier, David C.; Huguenard, Anna L.; Srienc, Anja I.; Cler, Samuel J.; Osbun, Joshua W.; Chatterjee, Arindam R.; Vellimana, Ananth K.; Kansagra, Akash P.; Derdeyn, Colin P.; Cross, Dewitte T.; Moran, Christopher J. (Frontiers in Neurology, 2023)
Tools and techniques utilized in endovascular brain aneurysm treatment have undergone rapid evolution in recent decades. These technique and device-level innovations have allowed for treatment of highly complex intracranial aneurysms and improved patient outcomes. We review the major innovations within neurointervention that have led to the current state of brain aneurysm treatment.